Community PrEP delivery for adolescent girls and young women: insights from the DREAMS PrEP Choice Study in Johannesburg, South Africa - Nicolette Prea Naidoo; Nqaba Mthimkulu; Ngcwalisa Jama; Glory Chidumwa; Brison Chabalala; Tafadza Mhakakora; Lauren Parmley; Saiqa Mullick (Frontiers in Reproductive Health)
IntroductionLong-acting pre-exposure prophylaxis (PrEP) methods have the potential to significantly reduce HIV acquisition and increase the uptake and effective use of PrEP among adolescent girls and young women (AGYW). We describe the implementation approach for delivering the PrEP ring and outline provider perspectives related to community-based service delivery.MethodsThe DREAMS PrEP Choice Study, a mixed-methods implementation science study delivering PrEP choice to women 18 years and older, was conducted in Johannesburg, South Africa. We extracted quantitative enrollment data from the routine patient management system (REDCap) and collected qualitative data from four focus group discussions with providers. Quantitative data are presented descriptively whilst qualitative data were analyzed using content and thematic analyses.ResultsBetween October 2023 and April 2024, 657 participants were enrolled and offered PrEP choice. Most (72.1%, n = 474) participants were between 18 and 24 years old and accessed services at education and training institutions (52.1%, n = 342). Furthermore, 68.8% (n = 451) chose oral PrEP at enrollment, 26.6% (n = 175) chose the PrEP ring, and 3.2% (n = 20) selected no method. Most participants accessed services through a mobile truck (n = 365, 55.6%). There was a strong preference for nurse insertion of the ring on site (n = 103, 58.9%). Site setup, privacy, and access to running water, in alignment with national PrEP ring guidelines, were reported as barriers to implementation.ConclusionAs one of the first studies to implement community-based services for PrEP choice, the early results indicate the feasibility of delivering this service with moderate uptake of PrEP by AGYW. Understanding the service delivery conditions required to offer informed choice is important for supporting national scale-up.